Trust in independent community pharmacies: Do employee-related factors matter? - Edwin Theron; Almeri Pelser (AOSIS, 2020)
Background: Offering quality healthcare services in South Africa's remote areas remains a challenge. Pharmacies, and independent community pharmacies (ICPs) in particular, can play a vital role in providing access to pharmaceutical products and services in these areas. Aim: Part of the success of ICPs is the role that their employees play in building trusting relationships with pharmacy clients. It is against this background that this article investigates key employee-related factors that contribute towards building affective, calculative and contractual trust when pharmacy clients are serviced. Setting: Clients of a specific ICP group participated in the study. The selected ICP group, which manages eight pharmacies across the Western Cape Province, has between 8000 and 41 000 active client profiles per pharmacy. Methods: All 299 respondents who participated in the study were personally interviewed. Statistical analyses were done through Statistica, and structural equation modelling (SEM) with partial least squares (PLS) was used to assess both the measurement and the structural model. Results: Although a number of significant relationships were confirmed, the importance of especially familiarity is highlighted when trust is managed in a pharmacy client-employee relationship. Conclusion: Given their geographical location, ICPs are ideally situated to provide access to healthcare services in the more remote areas of South Africa. By focusing on managing trust, ICPs can ensure a more constructive experience to their clients.